FRI0593-HPR Translation, cultural adaptation and reproducibility of the michigan hand outcomes questionnaire (MHQ) for brazil. (23rd January 2014) - Adolph, S. M. M.; Natour, J.; Batista, D. A.; Lopes, M.; Skare, T. L.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease that affects all synovial joints causing progressive and irreversible joint destruction. Hand dysfunction and deformities are some of the most common manifestations of this disease and they are an important cause of morbidity as they interfere with the capacity to perform self care, work productivity and social interactions. MHQ (Michigan Questionnaire of Hand Evaluation) is a hand evaluation instrument that has been conceived at University of Michigan in 1998 using psychometric principles Objectives: To translate to Portuguese, to perform cultural adaptation and to test the reliability of the questionnaire Function Hand Outcomes Questionnaire hand Michigan (MHQ) for use in the Brazilian population. Methods: In the first stage of the study, the MHQ was translated into Portuguese and back translated into English. The Portuguese version was tested in 30 patients with rheumatoid arthritis with some involvement in hand or wrist and the questionnaire proved to be understandable and culturally adapted. In a second stage of the study, 30 patients with rheumatoid arthritis with hand or wrist affected were evaluated 3 times. In the first two evaluators applied the MHQ to check intra rater reliability. After 15 days, one of the evaluators reinterviewed the patients to verify inter-rater reproducibility. To check the construct validity at the the first assessment, one of the evaluators also applied other instruments such as DASH (Disability of the Arm, Shoulder and Hand questionnaire), HAQ (Health Assesment Questionnaire), VAS (Visual Analogic Scale) of pain and COCHIN Hand Function Scale. Results: We observed strong inter and intra rater correlations in all areas of the MHQ. Intra rater concordance ranged from 0.84 to 0.96 and inter rater correlations ranging from 0.61 to 0.92. The Cronbach's alpha was higher than 0.90 for all domains of the MHQ indicating that the questionnaire had good internal validity. Almost all domains of the MHQ evaluation applied to the dominant hand presented moderate and strong correlation (r ranging from -0.50 to -0.89) with other instruments showing a good construct validity. Conclusions: The Brazilian Portuguese version of the MHQ was translated, culturally adapted successfully and showed very good internal consistency, reliability and construct validity. Disclosure of Interest: None Declared